Performance Analysis and Optimization of a Microstrip Parallel Coupled Line Bandpass Filter for C-Band Satellite Receiver Applications - Moe Myint Aung; Hla, Tin Tin (AI Society & STMIK Indonesia, 2025)
The design and optimization of a microstrip parallel coupled line bandpass filter (BPF) for C-band satellite receiver applications are the main focus of this work. Various filter orders (third order to seventh order) were analyzed and compared based on key performance parameters, including insertion loss, return loss, bandwidth, and shape factor. The optimized fifth order filter was selected as the most suitable due to its low insertion loss of -0.625 dB, deep return loss of -31.443 dB, and adequate bandwidth of 565 MHz, ensuring efficient signal transmission with minimal reflection. The calculated shape factor of 1.7 indicates a sharp roll-off, enabling effective rejection of out-of-band interference while maintaining a well-defined passband. The proposed design achieves a balance between performance, complexity, and real-world applicability, making it a reliable and efficient solution for C-band satellite communication systems.